CHRONIC KIDNEY DISEASE AND CARDIOVASCULAR DISEASES: FOCUS ON ATRIAL FIBRILLATION - V. N. Shishkova (Рациональная фармакотерапия в кардиологии, 2015)
The question of mutual influence of risk factors for cardiovascular and renal diseases with a focus on atrial fibrillation is considered. Modern approaches to the prevention of major macrovascular events in patients with comorbidity are evaluated.